UJI EFEK PENYEMBUHAN LUKA FASE MINYAK EKSTRAK IKAN TOMAN (Channa micropeltes) PADA TIKUS PUTIH JANTAN WISTAR YANG DIBERI LUKA SAYAT - ., Afrian Rahmanda (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
The striped snakehead (Channa striata) has been approved can heal cuts and it is s in the same family with Giant snakehead (Channa micropeltes). The giant snakehead oil consists of fatty acid-3and fatty acid-6 and also some other fatty acids which is can help to cure wound healing. Thisresearch aimed to determine the effect of giant snakehead oil which is can help to cure the cuts andthe best dose of giant snakehead oil to accelerate healing process of cuts which is given orally. 15white male Wistar rats (Rattus novergicus) which are divided into 5 groups, there are group 1 asnegative control), group 2 (0,15 ml/kg the rat weight), group 3 (0,3 ml/kg the rat weight), group 4(0,57 ml/kg the rat weight and group 5 as comparison. Each group was given cut on their back with alength of 2 cm, except for the group 5. Then, each group was given the giant snakehead oil for 7 daysand also get controlled of the wound areaÂ  on day 0, 1, 3 , 5 and 7. The wound area was measured byusing a programme, that is Macbiophotonic Image J. The data were analyzed by SPSS for Windows17.0 and using One Way ANOVA and also Post-Hoc Tukey HSD test. There are the significantdifferences on day 5 and day 7 (p < 0,05) between all of groups). This result shows that the usage ofgiant snakehead oil can help to cure the wound healing. The dose of 0,57 ml/kg the rat weight has thebest effect in healing process of cuts than group 3 and group 2. The percentage is about 93,19%, forgroup 3 (0,3 ml/kg the rat weight) is about 87,30% and for the group 2 (0,15 ml/kg the rat weight) is79,43% Keywords : Giant snakehead extract, oil based, cuts, fatty acids